Review Literatur: Faktor yang Mempengaruhi Penemuan Kasus Tuberkulosis - Maqh Ferotillah; Hamzah Hasyim; Rizma Adlia Syakurah (Lembaga Pengembangan Kinerja Dosen, 2025)
Tuberculosis (TB) remains a global public health problem with low case detection rates, especially in developing countries including Indonesia. Low TB detection hinders efforts to eliminate TB by 2035. This study aims to review the factors that influence TB case detection based on the results of research conducted over the past five years. The method used was a literature review with articles retrieved from PubMed, ScienceDirect, and Google Scholar for the period 2019–2024. The inclusion criteria included studies discussing individual, socioeconomic, environmental, and health system factors affecting TB detection. A total of 15 articles met the criteria and were analyzed thematically. The results showed four main groups of factors that influence TB case detection, namely: (1) individual factors such as knowledge, stigma, and seeking treatment behavior; (2) socioeconomic factors including poverty, education, and access to health services; (3) environmental factors such as housing density and home ventilation; and (4) health system factors including workforce competence, diagnostic facilities, and reporting systems (Gunawan et al., 2022; Mohammed et al., 2023; Liu et al., 2024). In conclusion, efforts to increase TB case detection require a multidimensional approach through strengthening the capacity of health workers, community empowerment, environmental improvement, and cross-sector collaboration. This sustainable strategy is important to achieve the WHO's End TB Strategy 2035 target (WHO, 2023).